DESIGN AND CONSTRUCTION OF 500W SOLAR GENERATOR KIT - Zaharaddden, Musa; Aliyu, Bello (FUDMA JOURNAL OF SCIENCES, 2025)
In response to the unreliable electricity supply in Dutsin-ma, Katsina State, this study proposes a clean and sustainable alternative to petrol and diesel generators widely used across Nigeria. The aim is to design and build a 500W solar generator kit that is cost-effective, eco-friendly, and capable of meeting typical household energy needs. The system is designed to power essential appliances such as a DC fan, mobile phones, a laptop, and five DC bulbs. The solar generator kit includes a 100W photovoltaic (PV) panel, a 12V 20Ah battery, a 20A charge controller, and a 500W inverter. These components are housed in a compact, custom-made metal frame measuring 14" x 9" x 7", with both AC and DC output ports for versatile use. Weighing 20kg, the unit is portable and ideal for off-grid environments. Performance tests showed that the generator could provide continuous power for up to 6 hours under a 450W load, delivering stable 230V AC and 12V DC outputs. It charges fully in 6–8 hours of direct sunlight, achieving an average efficiency of 85%. This project offers a sustainable power solution that can improve energy access while reducing environmental impact.